Creating Math Videos: Comparing Platforms and Software. Issue 2 (7th February 2016) - Abbasian, Reza O.; Sieben, John T.
Abstract: In this paper we present a short tutorial on creating mini-videos using two platforms—PCs and tablets such as iPads—and software packages that work with these devices. Specifically, we describe the step-by-step process of creating and editing videos using a Wacom Intuos pen-tablet plus Camtasia software on a PC platform and using the software Doceri with iPads to produce instructional math videos. We then focus on the merits and shortcomings of each platform. We conclude this paper by discussing the hardware and software requirements for presenting these videos in a classroom. This article is intended for mathematics and/or statistics educators with an interest in using instructional videos, online resources, and the flipped classroom approach to teaching, and is appropriate for the newcomer to the flipped classroom as well as more seasoned practitioner.